Dualistiese antropologie by Paulus? - Pelser, G. M. M. (Hervormde teologiese studies, 2000)
Dualistic anthropology in Paul? The question as to whether Paul's anthropology can be qualified as dualistic is, with a few exceptions, usually answered in the negative. However, although the vast majority of scholars favour the negative answer, it cannot be denied that there are instances in the Pauline correspondence which are suspect, to say the least. It is for this reason that the debate has not come to a rest yet, and that the issue is still raised from time to time. The present study was prompted by recent contributions to the debate, especially those of Boyarin (1994) and Crossan (1998), in which it is claimed that Paul's anthropology can indeed be qualified as dualistic. The outcome of the study is that one has every reason to believe that in a number of passages Paul not only made use of dualistic terminology and concepts, but that he actually also conceived of human existence in a dualistic manner.